Meningkatkan Kemampuan Menyelesaikan Masalah Belajar Siswa SMK Dengan Layanan Bimbingan Teknik Problem-Based Introduction - Wijayanti, Wijayanti (Universitas Nusantara PGRI Kediri, 2019)
The ability to solve vocational student learning problems is an important element in achieving optimal learning achievement and everyday life. The importance of this ability is not yet optimal among SMK students. To improve these capabilities, researchers need to use classical guidance services with problem-based introduction techniques that are relevant to the abilities to be achieved. Thus the purpose of this study is to find out the application of guidance services with problem-based introduction techniques to improve the ability to solve vocational student learning problems. To achieve this goal, researchers used the action research method in BK (PTBK) for two cycles of 50 students, drawn from a population of 2004 vocational school students by purposive sampling. The results of this study indicate the achievement of criteria as much as 46% in the first cycle, and the remaining 64% was achieved in the second cycle. With this achievement, it can be concluded that the guidance service with problem-based introduction techniques can be applied to improve the ability to solve vocational student learning problems.